3-R-4-(5-Methyleneazide-1, 2, 4-oxadiazol-3-yl)furazan and its ionic salts as low-sensitivity and high-detonation energetic materials. (14th June 2021) - Yang, Rui; Liu, Yifei; Dong, Zhen; Li, Haiyan; Ye, Zhiwen
Abstract : 3- R -4-(5-Methyleneazide-1, 2, 4-oxadiazol-3-yl)furazan compounds as low-sensitivity and high-detonation energetic materials. Abstract : As an environmentally friendly energetic group, the azide group can not only control the melting point but also increase the energy of the compound. Therefore, the design and synthesis of energetic compounds with azido groups have long been a focus of research in the field of energetic materials. 3- R -4-(5-methyleneazide-1, 2, 4-oxadiazol-3-yl)furazan energetic materials were synthesized and fully characterized. Using computational chemistry methods, the interactions of some compounds were studied, and the physical and chemical properties of all of compounds were examined. The results show that 3-amino-4-(5-methyleneazide-1, 2, 4-oxadiazol-3-yl)furazan (2 ) has a melting point similar to that of TNT and can be a potential carrier for molten-cast explosives. Hydroxylamine salt (4 ) has an excellent detonation velocity and detonation pressure of 9090 m s −1 and 35.76 GPa, respectively, and its energy is significantly higher than that of RDX, enabling replacement of RDX as a high-energy explosive. Although the detonation performance of compound 4 is slightly lower than that of HMX, its sensitivity is better than that of HMX, which shows that compound 4 still has a high application value. Non-covalent interactions (NCIs) and Hirshfeld surface models indicate that hydrogen bonding and π–π interactions are the key factors that reduce the sensitivity of compounds. Therefore, our results for 3- R -4-(5-methyleneazide-1, 2, 4-oxadiazol-3-yl)furazan energetic materials suggest that it may be competitive for application in both molten-cast explosives and high-energy explosives.